A eficiência relativa da governança eletrônica das universidades federais brasileiras - Barros, Ana Paula da Cruz Holanda (2017)
The reinvention of the State, with regard to providing services, namely, the dissemination of information and interaction with the various social actors, has given rise to the phenomenon of electronic governance or e-governance (EG) in the context of public management. Considering that e-governance can support good management practices in public administration and, more importantly yet, that it has the power to bring citizens closer to the sphere of governance and government decision-making, this study has as its major goal to measure, through the application of a formal efficiency evaluation method, the Data Envelopment Analysis (DEA), the relative efficiency of electronically directed management as seen in Federal Universities of Brazil. To reach the goals, researchers adopted a quantitative approach, with a descriptive purpose using documental research procedures. As for data collection, the GE measurement was used to obtain the electronic governance index of universities called EGIU. The universe of the research contemplated 63 Brazilian federal universities, being the sample of the census type. With regard to data analysis, this study resorted to the Data Envelopment Analysis (DEA) technique by choosing the model of variable returns instead of the product-oriented scale (BCC) to test the relative efficiency of EG, using the computational tool Frontier Analyst for data treatment. Thus, the results show that 14.28% of the universities reached the efficiency frontier, corresponding to nine institutions, and 85.71% were considered inefficient, representing 54 universities. It was found that the Northeast region, in percentage terms, was the most efficient with 22% of its universities considered efficient. The Central-West region was the most inefficient since no institution reached the efficiency frontier. The study of measuring practices applied to e-governance also showed that the Services class had the highest adhesion rates among universities, while the Citizen Participation class registered the lowest rate of adherence.